Development of a tool to calculate the probability of hypocalcemia after total thyroidectomy: a prospective study - Soares, Carlos Segundo Paiva [UNESP] (2024)
Purpose: This study aimed to evaluate the ability of the percentage of decrease in serum PTH level in the first 8 h after total thyroidectomy (TT) to predict hypocalcemia requiring Ca supplementation and develop a tool to predict it. Methods: 97 patients who underwent TT with measurement of preoperative parathyroid hormone (PTH) levels were prospectively evaluated 1 and 8 h after TT; postoperative magnesium (Mg2PO) and phosphorus levels were evaluated on the 2nd day after surgery. The percentage of decrease in PTH level 1 h (%dPTH1h) and 8 h (%dPTH8h) postoperatively and predictors of hypocalcemia requiring Ca supplementation were evaluated and an equation was developed to predict this outcome. Results: %dPTH1h (p = 0.002), %dPTH8h (p = 0.001) and (Mg2PO) (p < 0.01) were isolated predictors of postoperative hypocalcemia requiring Ca supplementation. The data obtained led to the development of two tools to predict this complication. Conclusions: The percentage of decrease in PTH level 1 h and 8 h postoperatively and the magnesium level on the 2nd day after surgery were predictors of more severe hypocalcemia, and an auxiliary tool for predicting this complication was developed.